A New Path to Address Multimorbidity? Longitudinal Analyses of Retirement Sequences and Chronic Diseases in Old Age. (April 2022) - Calvo, Esteban; Azar, Ariel; Shura, Robin; Staudinger, Ursula M.
Chronic disease and multimorbidity are growing health challenges for aging populations, often coinciding with retirement. We examine late-life predictors of multimorbidity, focusing on the association between retirement sequences and number of chronic diseases. We modeled the number of chronic diseases as a function of six types of previously identified 10-year retirement sequences using Health and Retirement Study (HRS) data for 7, 880 Americans observed between ages 60 to 61 and 70 to 71. Our results show that at baseline, the adjusted prevalence of multimorbidity was lowest in sequences characterized by late retirement from full-time work and highest in sequences characterized by early labor-force disengagement. Age increases in multimorbidity varied across retirement sequences, though overall differences in prevalence persisted at age 70 to 71. Earlier life disadvantages did not moderate these associations. Findings suggest further investigation of policies that target health limitations affecting work, promote continued beneficial employment opportunities, and ultimately leverage retirement sequences as a novel path to influence multimorbidity in old age.